WAYANG PANDAWA COMIC AS EDUCATION MEDIA FOR CHILDREN CHARACTER - Wiekandini Dyah Pandanwangi; Zulisih Maryani (Program Studi Pendidikan Bahasa Inggris Fakultas ilmu Budaya, 2023)
Wayang (puppet) has been embodied in Indonesian especially Javanese life. Wayang contains local wisdom which is important for Indonesian character building and identity and it is manifested through its plot and characters. Local wisdom-based character building as Indonesian identity is significant for young generation to create an intelligent, virtuous, and good personality generations. One of ways to build a character in children is by internalizing local wisdom through introducing wayang stories and characters. All characters in wayang are adapted from the original character of Indonesian people. The life philosophy embodied in wayang through the stories and characters are significantly comprehended for deep and useful essence for life. Particularly, it is necessary to be introduced to elementary students. By doing so, a wayang comic is proposed in this research as the education media for children character building.